Protein epitope mimetic macrocycles as biopharmaceuticals. (June 2017) - Luther, Anatol; Moehle, Kerstin; Chevalier, Eric; Dale, Glenn; Obrecht, Daniel
Graphical abstract: Highlights: Medium-sized macrocycles can address novel disease-relevant targets. Protein epitope mimetics (PEM) are mimics β-hairpin and α-helical protein epitopes. PEM molecules can be efficiently synthesized using high-throughput parallel synthesis. A summary of PEM molecules in clinical development is given. Abstract : Fully synthetic medium-sized macrocyclic peptides mimicking the key β-hairpin and α-helical protein epitopes relevant in many protein–protein interactions have emerged as a novel class of drugs with the potential to fill an important gap between small molecules and proteins. Conformationally stabilized macrocyclic scaffolds represent ideal templates for medicinal chemists to incorporate bioactive peptide and protein pharmacophores in order to generate novel drugs to treat diseases with high unmet medical need. This review describes recent approaches to design and generate large libraries of such macrocycles, for hit identification, and for their efficient optimization. Finally, this review describes some of the most advanced protein epitope mimetic (PEM) macrocycles in clinical development.